PERFORMA SOSIAL EKONOMI PETANI PADI SAWAH LEBAK DALAM ADOPSI TEKNOLOGI SISTEM TANAM PADI IP 200 DI KOTA PALEMBANG - Azmi, Nur; Umikalsum, RA; Febriyansyah, Ahmad (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Kelautan Universitas Bangka Belitung, 2024)
Increasing the rice planting index (IP) can contribute to increasing rice production and food security. The intensity of rice planting in Lebak rice fields is currently still once a year, even though IP200 has been introduced for 6 years, so identification and comparison analysis of the social and economic performance of farmers who apply IP200 is needed. The sampling method used was Disproportionated Stratified Random Sampling, where the level of stratification was represented by 17 farmers who implemented the IP200 rice planting system technology innovation and 17 farmers who did not. Data analysis using farming analysis and business risk analysis. The results of data analysis are that the social rationality of age, education, number of family members and regional origin are not different, while the variable of farmer experience can influence the enthusiasm of farmers to implement it, the variables of farmer status as cultivators, pest attacks, extension activity, and higher motivation for farmers who implementing IP 200. Economic performance on land area variables greatly influences production and income, thus helping farmers with capital to implement IP200.